Watu Kuém: os Borum do médio rio Doce, o evento crítico de Mariana e o encontro pragmático com o Direito - João Vitor de Freitas Moreira (2020)
The present work aims to verify the meanings of the death of Doce rive – what is called by the Borum people of eastern Minas Gerais as Watu Kuém – and the repercussion of the Fundão dam disaster in 2015 into the field of law. To this end, an empirical research is developed in the attempt to take seriously the native's concept and relationships, and it is contrasted such responses with the legal framework of the critical event. After 7 months of empirical incursion and dialogues with the indigenous people, the native relations is framed into the Eduardo Viveiros de Castro's Amerindian perspectivism. Then, in the quest for native legal sensibility, this perception is contrasted with the Public Civic Actions that gained prominence in the attempt to repair the damage in what came to be known as the “Mariana case”. Finally, we conclude about the difficulties of tracing a legal sensibility of the Borum people and we point out other ways in the interlocutions of this indigenous people with the law that has ontological repercussion, and it is presented a reading of law as a pragmatic encounter of ways of imagining the real.